Analysing teachers' operations when teaching students: what constitutes scientific theories?. Issue 7 (3rd May 2017) - Holmqvist, Mona O.; Olander, Clas
ABSTRACT: The aim of the study is to analyse teachers' efforts to develop secondary school students' knowledge and argumentation skills of what constitutes scientific theories. The analysis is based on Leontiev's three-level structure of activity (activity, action, and operation), as these levels correspond to the questions why, what, and how content is taught. The unit of analysis was a school development project in science education, where design-based interventions were conducted. Data comprised notes and minutes from eight meetings, plans, and video recordings of the lessons, and a written teacher evaluation. The teachers' ( n = 7) learning actions were analysed to identify (a) concept formation in science education, (b) expressions of agency, (c) discursive manifestations of contradictions, and (d) patterns of interaction during the science interventions. Three lessons on what constitutes scientific theories were implemented in three different student groups ( n = 24, 23, 24), framed by planning and evaluation meetings for each lesson. The results describe (1) the ways in which teachers became more skilled at ensuring instruction met their students' needs and (2) the ways in which teachers' operations during instruction changed as a result of their developed knowledge of how to express the content based on theoretical assumptions.